Pemetaan Indeks Kesehatan Vegetasi dengan Menggunakan Data Penginderaan Jauh dan Sistem Informasi Geografis pada Kondisi El Nino, La Nina dan Normal di Provinsi Bali - IDA AYU PUTU JELANTIK PARWATI; I WAYAN NUARSA; R. SUYARTO (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Mapping of Vegetation Health Index Using Remote Sensing Data and Geographical Information Systems in El Nino, La Nina and Normal Conditions in Bali Province This research is about mapping the vegetation health index using Terra Modis level 3 imagery in Bali Province in El Nino conditions in 2015, La Nina in 2016, and normal in 2017. The purpose of this research is (1) to calculate the vegetation health index in El Nino, La Nina and normal, (2) to map the distribution of drought in El Nino, La Nina, and normal conditions, and (3) to know the effects of El Nino, La Nina, and normal conditions on food crop production in Bali Province. The results showed that the vegetation health index in Bali Province was observed based on the drought class. There were 5 drought classes in 2015, 2016 and 2017. The most widespread extreme and strong drought occurred in the 2015 El Nino phenomenon with an area of ??152, 900 ha, followed by normal conditions in 2017 with an area of ??20,100 ha, and the smallest area was in 2016 with area of ??10,100 ha. Temporally, the level of drought in Bali Province in El Nino, La Nina and Normal conditions occurs in September and peaks in October and November, and decreases in December. Spatially, drought occurs in the southern, western, northern and eastern parts of Bali, meanwhile, in the central part, there is generally no drought. The highest production of food crops in Bali Province is shown by data in 2016, followed by production in 2015, and the lowest in 2017. Statistically, through the paired t-test, the El Nino and La Nina phenomena do not have a significant effect on food crop production compared to normal conditions.